Interdependence through geophysical fluids: Saharan haze and other oceanic and atmospheric phenomena - Watlington, Roy A.
In this paper, the Saharan haze and other phenomena are used as examples of linkages forged between the people of the Caribbean by the forces of nature and the acts of people. An attempt is made to demonstrate how increased understanding of the laws of nature may lead to greater utilization of science among both the people and their leaders, and may create a new perspective in decision making in public health, international commitments, and national security. A case is also made for promoting understanding of the concept of a geophysically interdependent Caribbean among the people of the region. This premise of geophysical interdependence leads to the conclusion that only by sharing scientific knowledge, and human and other resources in science and technology, can Caribbean countries benefit rather than suffer when interacting with, or seeking to alter nature
Special Issue: Environmental education: Global concern, Caribbean focus, ed. by Joyce Glasgow
Keywords: Geophysics